Well-being and Capability Approaches to Social Injustice in Internationalization of Higher Education: Evidence from Vietnam - Huu Thanh Minh Nguyen; Hoang My Thieu (Training and Research Institute Jeramba Ilmu Sukses (TRI - JIS), 2023)
This mixed-method study investigated social injustice in higher education produced from the internationalized high-quality program (HQP) characterized by adapting the curriculum from prestigious universities abroad and employing English as the medium of instruction in Vietnam, based on White’s (2010) well-being approach as well as Sen’s (2001) capability approach. Using the questionnaire administered to 120 students and 30 lecturers and semi-structured interviews conducted with eight students in a university in Vietnam, the findings suggested that from subjective dimensions of well-being, the superior features of the HQP and pre-sessional English language training were perceived values of endowments that HQP students and their parents situated themselves in. That established a solid linkage to material dimensions reflected in the possibility of securing the economy after program completion. From the capability approach perspective, although such a disparity in endowments was unjustifiable due to problematic program delivery, there were no different entitlements that might have led to social injustice, providing that students of any program could fulfil their education. The issue of financial affordability relating to the HQP implementation has raised concern about unequal access to educational opportunities for all.